Foaming curable composition

By adding components such as thermoset elastomers, chemical foaming agents and expandable particles to the foaming filler, the problem of insufficient foaming after uncured placement in the prior art is solved, and good under high temperature or wet conditions is achieved Sound insulation and automatic coating ease.

CN119137199APending Publication Date: 2024-12-13SUNSTAR GIKEN KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380038239.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-11
Filing Date
2023-04-21
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The foaming properties of the existing coating foaming fillers are insufficient after uncured and placed under high temperature or wet conditions, resulting in deterioration of working properties and unable to fully exert sound insulation effect.

Method used

The foam curable composition including thermoset elastomer, chemical foaming agent, expanded particles with shell and inner wrapping components, crosslinking agent and other components is used to ensure that it has good foaming and bonding after uncured placement. sex.

Benefits of technology

The viscosity and foaming ratio of the foam curable composition are improved, ensuring that good sound insulation performance can be maintained under high temperature or humid conditions, simplifying the automated coating process, and improving workability and sound insulation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005116765630000231
    Figure BDA0005116765630000231
  • Figure BDA0005116765630000261
    Figure BDA0005116765630000261
  • Figure BDA0005116765630000271
    Figure BDA0005116765630000271
Patent Text Reader

Abstract

The present invention provides a novel foam curable composition containing a thermosetting elastomer (A), a chemical foaming agent (B), and expandable particles (C) having a shell and an inner component containing a hydrocarbon (C1) having 7-9 carbon atoms, the foam curable composition having a foam characteristic and an adhesive characteristic, and having a heat-insulating property, a heat-insulating property, and a heat-insulating property, in addition to the foam characteristic and the adhesive characteristic, and a heat-insulating property, a heat-insulating property, a heat-insulating property, and a heat-insulating property, in addition to the heat-insulating property, a heat-insulating property, and a heat-insulating property. Good characteristics after uncured placement are also realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a foaming curable composition, and in particular to a foaming curable composition useful for improving the sound insulation properties of an article. Background Art

[0002] The gaps in various articles can be the cause of noise. For example, for a vehicle, when driving, air invades the cavity column of the vehicle component and generates wind noise, which hinders the quietness of the driving part. In order to isolate such noise, it is known that there is a technology of pasting a foamable molded product in the gap and then filling the gap by heating and foaming. However, there are problems such as the manufacturing cost of the molded product and the difficulty of automating the pasting, which may not be economical. In addition, when using a foamable molded product, restrictions are generated in the foaming direction, and the filling of the foaming filler becomes insufficient and the sound insulation effect cannot be fully exerted. In view of such a situation, in recent years, the use of a coated foaming filler instead of a foamable molded product is being studied.

[0003] Patent Document 1 discloses a paste-like heat-foamable filling material characterized by containing an uncrosslinked rubber, a quinone-based vulcanizing agent, and a foaming agent, and having high foaming performance even at low temperatures.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2012-136135 Summary of the invention

[0007] Technical problem to be solved by the invention

[0008] However, the foaming properties of the existing coating type foaming fillers after being left uncured (for example, the foaming properties after being left uncured under high temperature conditions and / or wet conditions) are not necessarily sufficient. In the case where the foaming properties after being left uncured are insufficient, the workability deteriorates and becomes disadvantageous. Therefore, the present invention provides a novel foaming curable composition, which has good foaming properties after being left uncured in addition to foaming properties and adhesive properties.

[0009] Solutions for solving technical problems

[0010] The present invention comprises the following scheme:

[0011] [Project 1]

[0012] A foamable curable composition, wherein the foamable curable composition comprises

[0013] Thermosetting elastomer (A),

[0014] Chemical blowing agent (B), and

[0015] Expandable particles (C) having a shell and an inner component,

[0016] The inner component includes hydrocarbons having 7 to 9 carbon atoms (C1).

[0017] [Project 2]

[0018] The foamable curable composition according to item 1, wherein the average boiling point of the internal component is 50° C. or higher and 130° C. or lower.

[0019] [Item 3]

[0020] The foamable curable composition according to item 1 or 2, wherein the hydrocarbon (C1) has a boiling point of 80° C. or higher and 120° C. or lower.

[0021] [Item 4]

[0022] The foamable curable composition according to any one of items 1 to 3, wherein the hydrocarbon (C1) contains isooctane.

[0023] [Item 5]

[0024] The foamable curable composition according to any one of items 1 to 4, wherein the foamable curable composition contains a crosslinking agent (D).

[0025] [Item 6]

[0026] The foamable curable composition according to any one of items 1 to 5, wherein the crosslinking agent (D) includes at least one selected from the group consisting of peroxides, quinones, and sulfur.

[0027] [Item 7]

[0028] The foamable curable composition according to any one of items 1 to 6, wherein the thermosetting elastomer (A) is a diene polymer.

[0029] [Item 8]

[0030] The foamable curable composition according to any one of items 1 to 7, wherein the foamable curable composition comprises a thermoplastic resin (E) and a plasticizer (F).

[0031] [Item 9]

[0032] The foamable curable composition according to any one of items 1 to 8, wherein the foamable curable composition has a shear rate of 20 sec at 23°C. -1 The viscosity at that time is 500 Pa·s or more and 3000 Pa·s or less.

[0033] [Item 10]

[0034] The foamable curable composition according to any one of items 1 to 9, wherein the foaming ratio of the foamable curable composition is 6.5 times or more and 15 times or less.

[0035] [Item 11]

[0036] The foamable curable composition according to any one of items 1 to 10, wherein the peak temperature difference defined by [foaming peak temperature of the chemical foaming agent (B)] - [expansion peak temperature of the expandable particles (C)] is -10°C or more and 40°C or less.

[0037] [Item 12]

[0038] The foaming curable composition according to any one of items 1 to 11, which is used for sound insulation.

[0039] [Item 13]

[0040] A structure having a portion filled with the foamable curable composition or a foamed cured product thereof according to any one of items 1 to 12.

[0041] [Item 14]

[0042] The structure according to item 13, wherein

[0043] The structure has a closed surface,

[0044] The closed surface is filled with the foamable curable composition or its foamed cured product,

[0045] The structure is a vehicle body component or a car.

[0046] Effects of the Invention

[0047] The foamable curable composition of the present invention has good foaming properties after being left uncured, in addition to foaming properties and adhesive properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 It is a schematic explanatory diagram showing the shape of a test piece for shower resistance evaluation.

[0049] Figure 2 It is a schematic diagram of a shower resistance evaluation device.

[0050] Figure 3 It is a schematic explanatory diagram of the arrangement in the cap filling property evaluation. DETAILED DESCRIPTION

[0051] <Foaming Curable Composition>

[0052] The foamable curable composition of the present invention comprises a thermosetting elastomer (A), a chemical foaming agent (B), and expandable particles (C) having a shell and an inner component.

[0053] [Viscosity of Foaming Curable Composition]

[0054] The foaming curable composition has a shear rate of 20 sec at 23 °C. -1 The viscosity of the foaming curable composition at 23°C can be 300 Pa·s or more, 500 Pa·s or more, 700 Pa·s or more, 1000 Pa·s or more, 1200 Pa·s or more, or 1500 Pa·s or more, preferably 500 Pa·s or more, and more preferably 700 Pa·s or more. The shear rate of the foaming curable composition at 23°C is 20 sec -1 The viscosity is 3500Pa·s or less, 3000Pa·s or less, 2500Pa·s or less, 2000Pa·s or less, 1500Pa·s or less or 1200Pa·s or less, preferably 3000Pa·s or less, more preferably 1500Pa·s or less. By being within the above range, automatic coating becomes easy and workability can be improved. The viscosity of the foaming curable composition can be adjusted by changing the amount of the components (for example, the amount of the thermosetting elastomer (A), the amount of the plasticizer (F), etc.). In particular, by having a viscosity above the above lower limit, the loss of the foaming ratio caused by the breaking of the bubble during foaming and expansion can be appropriately suppressed, and the foaming ratio can be appropriately controlled.

[0055] [Foaming ratio of foamable curable composition]

[0056] The foaming ratio of the foaming curable composition can be 4 times or more, 5 times or more, 6 times or more, 7 times or more, 8 times or more, 9 times or more, 10 times or more, 11 times or more or 12 times or more, preferably 5 times or more, more preferably 6.5 times or more. The foaming ratio of the foaming curable composition can be 25 times or less, 20 times or less, 18 times or less, 16 times or less, 14 times or less, 12 times or less, 10 times or less or 8 times or less, preferably 15 times or less, more preferably 12 times or less. By being within the above range, it is possible to achieve good foamability and sufficient foam strength. The determination of the foaming ratio can be as described in the embodiment. Here, as a curing condition, any one of 130°C × 20 minutes, 150°C × 20 minutes, 160°C × 20 minutes, 180°C × 20 minutes or 215°C × 20 minutes can be used. Among these curing conditions, the foaming ratio can be within the above range under at least one, preferably two or more, and more preferably three or more (e.g., three conditions of 130°C × 20 minutes, 150°C × 20 minutes, and 180°C × 20 minutes, three conditions of 160°C × 20 minutes, 180°C × 20 minutes, and 215°C × 20 minutes). Whether before or after uncuring, the foaming ratio is preferably within the above range.

[0057] [(A) Thermosetting elastomer]

[0058] The foaming curable composition contains a thermosetting elastomer (A) having a reactive double bond. "Thermosetting elastomer" is a polymer that forms a three-dimensional network structure by heating and increases elasticity or exhibits elasticity. Examples of thermosetting elastomers (A) include silicone elastomers, acrylic elastomers, epoxy elastomers, fluorine elastomers, polyurethane elastomers, diene polymers, and the like.

[0059] Thermosetting elastomer (A) preferably has a reactive double bond, particularly preferably has a carbon-carbon double bond. Thermosetting elastomer (A) is preferably a diene polymer. The diene polymer may be a natural rubber or a synthetic rubber, and may have a repeating unit derived from butadiene or isoprene. As specific examples of diene polymers, acrylonitrile-isoprene copolymer rubber (NIR), acrylonitrile-butadiene copolymer rubber (NBR), styrene-butadiene copolymer rubber (SBR), butadiene rubber (BR), isoprene rubber (IR), etc. may be cited. The diene polymer may be an uncrosslinked rubber or a partially crosslinked rubber. The partially crosslinked rubber is a polymer obtained by partially crosslinking an uncrosslinked rubber using a crosslinking agent such as divinylbenzene or sulfur in advance. The thermosetting elastomer (A) is preferably solid at room temperature and can be dissolved and mixed in other liquid components in the composition for use. By selecting a thermosetting elastomer (A) that is solid at room temperature, it is possible to retain gas in the composition during foaming while ensuring physical properties after curing, thereby achieving good physical properties after curing and foaming characteristics.

[0060] (Amount of thermosetting elastomer (A))

[0061] The amount of the thermosetting elastomer (A) in the foaming curable composition may be 0.5% by weight or more, 1% by weight or more, 3% by weight or more, 5% by weight or more, 8% by weight or more, 10% by weight or more, 15% by weight or more, 20% by weight or more, or 25% by weight or more, preferably 3% by weight or more. The amount of the thermosetting elastomer (A) in the foaming curable composition may be 50% by weight or less, 45% by weight or less, 40% by weight or less, 35% by weight or less, 30% by weight or less, 20% by weight or less, or 10% by weight or less, preferably 40% by weight or less. When the amount of the thermosetting elastomer (A) is above the lower limit, the effect of suppressing gas escape can be well exerted. When the amount of the thermosetting elastomer (A) is below the upper limit, good viscosity can be exhibited.

[0062] [Chemical foaming agent (B)]

[0063] The foamable curable composition of the present invention contains a chemical foaming agent (B). The "chemical foaming agent" is a chemical agent that generates gas by thermal decomposition and generates foam in the composition.

[0064] The chemical foaming agent (B) may be an organic foaming agent or an inorganic foaming agent. The chemical foaming agent (B) may be aromatic or aliphatic. Examples of organic foaming agents include hydrazine foaming agents such as 4,4'-oxybis(benzenesulfonylhydrazide), 3,3'-disulfonylhydrazide diphenyl sulfone, allylbis(sulfonylhydrazide), and p-toluenesulfonylhydrazide; azo foaming agents such as azodicarbonamide (ADCA), azobisformamide, and azobisisobutyronitrile; fluorocarbon foaming agents such as trichloromonofluoromethane; semicarbazide foaming agents such as p-toluenesulfonyl semicarbazide; triazole foaming agents such as 5-morpholinyl-1,2,3,4-thiatriazole; and N-nitroso foaming agents such as N,N-dinitrosoterephthalamide. Examples of the inorganic foaming agent include ammonium carbonate, ammonium bicarbonate, ammonium nitrite, ammonium borohydride, and azides. The chemical foaming agent may be used in combination with a foaming aid (eg, urea).

[0065] (Foaming peak temperature of chemical foaming agent (B))

[0066] The "foaming peak temperature of the chemical foaming agent (B)" refers to the peak temperature accompanying foaming in the DSC curve with the horizontal axis being the temperature obtained by DSC measurement (temperature increase rate 20°C / min) of the foaming curable composition containing the chemical foaming agent (B). The detailed measurement method can be described in the Examples.

[0067] The peak temperature of the chemical foaming agent (B) and the expansion peak temperature of the expandable particles (C) described below may have a certain temperature difference, and the peak temperature difference defined by [the peak temperature of the chemical foaming agent (B)]-[the expansion peak temperature of the expandable particles (C)] is -10°C or higher, -5°C or higher, 0°C or higher, 1°C or higher, 3°C or higher, 5°C or higher, 10°C or higher, 15°C or higher, 20°C or higher, 25°C or higher, 30°C or higher, 35°C or higher, or 40°C or higher, preferably 0°C or higher, 5°C or higher, or 10°C or higher. The peak temperature difference defined by [the peak temperature of the chemical foaming agent (B)]-[the expansion peak temperature of the expandable particles (C)] is 100°C or lower, 90°C or lower, 80°C or lower, 70°C or lower, 60°C or lower, 50°C or lower, 40°C or lower, 30°C or lower, 20°C or lower, or 10°C or lower, preferably 50°C or lower, 40°C or lower, or 30°C or lower. When the content is within the above range, foaming properties, adhesive properties, and uncured left-standing properties can be satisfactorily achieved.

[0068] As in the case where the chemical foaming agent (B) is a combination of multiple types, when there are multiple peaks associated with foaming in the DSC curve, the temperature difference for at least one foaming peak temperature can be within the above range. The peak temperature difference for the maximum foaming peak temperature and / or for the average foaming peak temperature can be within the above range. The average foaming peak temperature can be the sum of the peak temperatures of multiple peaks associated with foaming multiplied by their peak area fractions. For example, the peak temperature of a DSC curve containing peak a (peak area Sa, peak temperature Ta) and peak b (peak area Sb, peak temperature Tb) is calculated based on the formula T = Ta × Sa / (Sa + Sb) + Tb × Sb / (Sa + Sb). It should be noted that the shoulder peak is also regarded as a peak, but it can be ignored if it is significantly smaller than the main peak.

[0069] The foaming peak temperature of the chemical foaming agent (B) may be 100° C. or higher, 120° C. or higher, 140° C. or higher, 160° C. or higher, 180° C. or higher, 200° C. or higher, or 220° C. or higher. The foaming peak temperature of the chemical foaming agent (B) may be 300° C. or lower, 280° C. or lower, 260° C. or lower, 240° C. or lower, 220° C. or lower, 200° C. or lower, 180° C. or lower, or 160° C. or lower.

[0070] (Amount of chemical foaming agent (B))

[0071] The amount of the chemical foaming agent (B) in the foaming curable composition may be 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, 3% by weight or more, 5% by weight or more, 8% by weight or more, 10% by weight or more, 15% by weight or more, or 20% by weight or more, or 25% by weight or more, preferably 1% by weight or more. The amount of the chemical foaming agent (B) in the foaming curable composition may be 45% by weight or less, 40% by weight or less, 35% by weight or less, 30% by weight or less, 20% by weight or less, or 10% by weight or less, preferably 30% by weight or less.

[0072] [(C) Expandable particles]

[0073] The foamable curable composition of the present invention may contain expandable particles (C). The expandable particles (C) have a shell and an inner component. When the expandable particles (C) are heated, the shell softens, and the inner component vaporizes and expands by heat, forming hollow particles (balloons).

[0074] The expandable particles are usually spherical (substantially spherical or ellipsoidal).

[0075] The average particle size of the expandable particles (C) may be 1 μm or more, 5 μm or more, 10 μm or more, 15 μm or more, 20 μm or more, 25 μm or more, 30 μm or more, 35 μm or more, 40 μm or more, or 50 μm or more, preferably 10 μm or more, and more preferably 20 μm or more. The average particle size of the expandable particles (C) may be 200 μm or less, 150 μm or less, 100 μm or less, 75 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less, preferably 100 μm or less, and more preferably 75 μm or less. Regarding the method for measuring the average particle size, the average particle size may be the 50% diameter of the volume cumulative particle size distribution measured by a laser diffraction / scattering particle size distribution measuring instrument.

[0076] Examples of commercially available expandable particles (C) include ADVANCELL EM series (Sekisui Chemical Co., Ltd.), Expancell DU, WU, MB, SL, and FG series (AkzoNovel Co., Ltd.), Matsumoto Microsphere F and FN series (Matsumoto Yushi Pharmaceutical Co., Ltd.), and KUREHA Microsphere (KUREHA Co., Ltd.).

[0077] (Expansion Peak Temperature of Expandable Particles (C))

[0078] The "expansion peak temperature of the expandable particles (C)" refers to the peak temperature accompanying expansion in the DSC curve of the expandable particles (C) obtained by DSC measurement (temperature increase rate of 20°C / min) with the horizontal axis being the temperature. The detailed measurement method can be described in the Examples.

[0079] The expansion peak temperature of the expandable particles (C) is lower than the foaming peak temperature of the chemical foaming agent (B), and as described in (Foaming Peak Temperature of Chemical Foaming Agent (B)) above, has a certain temperature difference from the foaming peak temperature of the chemical foaming agent (B).

[0080] As in the case where the expandable particles (C) are multiple combinations, when there are multiple peaks accompanying expansion in the DSC curve, the temperature difference for at least one expansion peak temperature only needs to be within the above range. The peak temperature difference for the maximum expansion peak temperature and / or for the average expansion peak temperature can be within the above range. The average expansion peak temperature can be the sum of the peak temperatures of multiple peaks accompanying expansion multiplied by their peak area fractions. For example, the peak temperature of the DSC curve containing peak a (peak area Sa, peak temperature Ta) and peak b (peak area Sb, peak temperature Tb) is calculated by the formula T = Ta × Sa / (Sa + Sb) + Tb × Sb / (Sa + Sb). It should be noted that the shoulder peak is also regarded as a peak, but it can be ignored when it is significantly smaller than the main peak.

[0081] The expansion peak temperature of the expandable particles (C) may be 80° C. or higher, 100° C. or higher, 120° C. or higher, 140° C. or higher, 160° C. or higher, 180° C. or higher, or 200° C. or higher. The expansion peak temperature of the expandable particles (C) may be 280° C. or lower, 260° C. or lower, 240° C. or lower, 220° C. or lower, 200° C. or lower, 180° C. or lower, 160° C. or lower, or 140° C. or lower.

[0082] (shell)

[0083] The shell constitutes the outer shell of the expandable particles (C). The shell is a material that softens by heating, particularly a thermoplastic resin.

[0084] The shell may have a repeating unit derived from a monomer. When simply referred to as a monomer, it means a polymerizable monomer having one polymerizable double bond (free radical), and is distinguished from a crosslinking monomer described below.

[0085] The shell may have a repeating unit derived from a nitrile monomer. A nitrile monomer is a monomer having one or more nitrile groups per molecule. Examples of nitrile monomers include acrylonitrile, methacrylonitrile, fumaric acid nitrile, α-ethyl acrylonitrile, α-isopropyl acrylonitrile, and the like. By including a nitrile monomer, the gas barrier properties of the thermoplastic resin constituting the shell can be improved.

[0086] The amount of repeating units derived from nitrile monomers in the shell may be 5% by weight or more, 15% by weight or more, 30% by weight or more, 45% by weight or more, or 60% by weight or more. The amount of repeating units derived from nitrile monomers in the shell may be 98% by weight or less, 95% by weight or less, 90% by weight or less, 80% by weight or less, 70% by weight or less, 60% by weight or less, or 50% by weight or less. The weight ratio (AN / MAN) of acrylonitrile (AN) and methacrylonitrile (MAN) may be 3 / 97 to 90 / 10, 4 / 96 to 70 / 30, or 4 / 96 to 60 / 40.

[0087] The shell may have repeating units derived from carboxyl-containing monomers. Carboxyl-containing monomers are monomers having one or more free carboxyl groups per molecule. Examples of carboxyl-containing monomers include unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, ethacrylic acid, crotonic acid, and cinnamic acid; unsaturated dicarboxylic acids such as maleic acid, itaconic acid, fumaric acid, citraconic acid, and chloromaleic acid; anhydrides of unsaturated dicarboxylic acids; unsaturated dicarboxylic acid monoesters such as monomethyl maleate, monoethyl maleate, monobutyl maleate, monomethyl fumarate, monoethyl fumarate, monomethyl itaconate, monoethyl itaconate, and monobutyl itaconate, and as preferred examples, acrylic acid, methacrylic acid, maleic acid, maleic anhydride, and itaconic acid, etc. As more preferred examples of carboxyl-containing monomers, acrylic acid and methacrylic acid can be cited, and as a particularly preferred example, methacrylic acid can be particularly cited due to its high gas barrier properties. A part or all of the carboxyl groups of the carboxyl group-containing monomer may be neutralized during or after polymerization.

[0088] The amount of repeating units derived from carboxyl-containing monomers in the shell may be 5% by weight or more, 15% by weight or more, 30% by weight or more, 45% by weight or more, or 60% by weight or more. The amount of repeating units derived from carboxyl-containing monomers in the shell may be 98% by weight or less, 95% by weight or less, 90% by weight or less, 80% by weight or less, 70% by weight or less, 60% by weight or less, or 50% by weight or less.

[0089] The shell may also have repeating units derived from other monomers. Examples of other monomers include halogenated vinyl monomers such as vinyl chloride; halogenated vinylidene monomers such as vinylidene chloride; vinyl ester monomers such as vinyl acetate, vinyl propionate, and vinyl butyrate; (meth)acrylate monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, stearyl (meth)acrylate, phenyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate; and acrylamide. , substituted acrylamide, methacrylamide, substituted methacrylamide and other (meth)acrylamide monomers; N-phenylmaleimide, N-cyclohexylmaleimide and other maleimide monomers; styrene monomers such as styrene and αα-methylstyrene; ethylene unsaturated monoolefin monomers such as ethylene, propylene, isobutylene; vinyl ether monomers such as vinyl methyl ether, vinyl ethyl ether, vinyl isobutyl ether; vinyl ketone monomers such as vinyl methyl ketone; N-vinyl carbazole, N-vinyl pyrrolidone and other N-vinyl monomers; vinyl naphthalene salts, etc.

[0090] As other monomers, it is preferred to include at least one selected from (meth)acrylate monomers, styrene monomers, vinyl ester monomers, acrylamide monomers and halogenated vinylidene monomers (particularly 1,1-dichloroethylene). When the shell contains repeating units derived from 1,1-dichloroethylene monomers, the gas barrier properties can be improved. When the shell contains repeating units derived from (meth)acrylate monomers and / or styrene monomers, it is easy to control thermal expansion characteristics. When the shell contains (meth)acrylamide monomers as a monomer component, heat resistance can be improved.

[0091] The amount of each monomer derived from at least one selected from vinylidene chloride, (meth)acrylate monomers, (meth)acrylamide monomers and styrene monomers may be 5% by weight or more, 15% by weight or more, 30% by weight or more, 45% by weight or more or 60% by weight or more in the shell. The amount of each monomer derived from at least one selected from vinylidene chloride, (meth)acrylate monomers, (meth)acrylamide monomers and styrene monomers may be 98% by weight or less, 95% by weight or less, 90% by weight or less, 80% by weight or less, 70% by weight or less, 60% by weight or less or 50% by weight in the shell.

[0092] In the case where the shell has a repeating unit derived from a carboxyl-containing monomer, the shell may have a repeating unit derived from a monomer reacting with the carboxyl group of the carboxyl-containing monomer. In the case where a monomer reacting with a carboxyl group is further included, heat resistance is further improved, and expansion performance at high temperatures is improved. As a monomer reacting with a carboxyl group, for example, N-hydroxymethyl (meth) acrylamide, N, N-dimethylaminoethyl (meth) acrylate, N, N-dimethylaminopropyl (meth) acrylate, vinyl glycidyl ether, acryl glycidyl ether, glycidyl (meth) acrylate, 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 2-hydroxybutyl (meth) acrylate, 2-hydroxy-3-phenoxypropyl (meth) acrylate, etc. can be cited. The amount of the repeating unit derived from the monomer reacting with the carboxyl group can be 0.1 to 10% by weight in the shell, for example, 3 to 5% by weight.

[0093] The shell may have a repeating unit derived from a crosslinking monomer having two or more polymerizable double bonds in addition to the above-mentioned monomers.

[0094] Examples of crosslinking monomers include aromatic divinyl compounds such as divinylbenzene; allyl methacrylate, 1,3,5-triacryloylhexahydro-1,3,5-triazine (triacrylformal), triallyl isocyanate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, PEG#200 di(meth)acrylate, PEG#600 di(meth)acrylate, trimethylolpropane trimethacrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol Hexaacrylate, di(meth)acrylate compounds such as 2-butyl-2-ethyl-1,3-propylene glycol diacrylate, bisacrylamides such as N,N'-methylenebis(meth)acrylamide; di- or tri(meth)acrylates obtained by reacting polyepoxide with (meth)acrylic acid; di(meth)acrylic acid urethanes obtained by reacting polyisocyanates such as toluene diisocyanate or hexamethylene diisocyanate with hydroxyethyl (meth)acrylate; allylated starch; allylated cellulose; diallyl phthalate; N,N',N"-triallyl isocyanurate; etc. These crosslinking agents can be used in combination of one or more.

[0095] The amount of repeating units derived from the crosslinkable monomer in the shell may be 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, 1% by weight or more, or 3% by weight or more. The amount of repeating units derived from the crosslinkable monomer in the shell may be 10% by weight or less, 7.5% by weight or less, 5% by weight or less, 3% by weight or less, or 1% by weight or less. The above range is preferred from the viewpoint of the expandability and heat resistance of the expandable particles (C).

[0096] ·Amount of shell

[0097] The amount of the shell in the expandable particles (C) may be 50% by weight or more, 60% by weight or more, 70% by weight or more, or 80% by weight or more. The amount of the shell in the expandable particles (C) may be 95% by weight or less, 90% by weight or less, 80% by weight or less, 70% by weight or less, or 60% by weight or less. The above range is preferred from the viewpoint of the expandability and heat resistance of the expandable particles (C).

[0098] (Ingredients included)

[0099] The inner component is a substance that is vaporized by heating and functions as a swelling agent in the expandable particles (C). The inner component contains a hydrocarbon (C1) having 7 to 9 carbon atoms.

[0100] The hydrocarbon (C1) having 7 to 9 carbon atoms may be a combination of a hydrocarbon having 7 carbon atoms and a hydrocarbon having 8 or 9 carbon atoms, a combination of a hydrocarbon having 8 carbon atoms and a hydrocarbon having 9 carbon atoms, or any one of 7, 8, and 9 carbon atoms. The hydrocarbon (C1) having 7 to 9 carbon atoms preferably includes a hydrocarbon having 8 carbon atoms. The hydrocarbon (C1) having 7 to 9 carbon atoms is preferably an aliphatic hydrocarbon, particularly preferably a saturated aliphatic hydrocarbon. The hydrocarbon (C1) having 7 to 9 carbon atoms may be linear, branched, or cyclic. Preferred specific examples of hydrocarbons (C1) having 7 to 9 carbon atoms include straight-chain or branched structural isomers of heptane such as n-heptane, 2-methylhexane, 3-methylhexane, 3-ethylpentane, 2,2-dimethylpentane, 2,3-dimethylpentane, 2,4-dimethylpentane, 3,3-dimethylpentane, and 2,2,3-trimethylbutane, and n-octane, 2-methylheptane, 3-methylheptane, 4-methylheptane, 2,2-dimethylhexane, 2,3-dimethylhexane, 2,4-dimethylhexane, 2,5-dimethylhexane, 3,3-dimethylhexane, and 2,2,3-trimethylbutane; Hexane, 3,4-dimethylhexane, 3-ethylhexane, 2,2,3-trimethylpentane, 2,2,4-trimethylpentane (isooctane) and other octanes, 2,3,3-trimethylpentane, 2,3,4-trimethylpentane, 2-methyl-3-ethylpentane, 3-methyl-3-ethylpentane, 2,2,3,3-tetramethylbutane, n-nonane, methyloctane, dimethylheptane, ethylheptane, trimethylhexane, ethylmethylhexane, tetramethylpentane, ethyldimethylpentane, diethylpentane and other nonanes. By including hydrocarbons (C1) having 7 to 9 carbon atoms (preferably 8 carbon atoms), expansion properties, adhesive properties, and uncured after-standing properties can be well exhibited.

[0101] The amount of hydrocarbons (C1) having 7 to 9 carbon atoms in the inner component may be 5% by weight or more, 10% by weight or more, 20% by weight or more, 40% by weight or more, or 60% by weight or more. The amount of hydrocarbons (C1) having 7 to 9 carbon atoms may be 95% by weight or less, 80% by weight or less, 70% by weight or less, 65% by weight or less, 50% by weight or less, or 30% by weight or less.

[0102] The inner component may contain inner components other than hydrocarbons (C1) having 7 to 9 carbon atoms. Examples of inner components other than hydrocarbons (C1) having 7 to 9 carbon atoms include hydrocarbons having 3 to 13 carbon atoms such as propane, butane, pentane, hexane, heptane, octane, nonane, decane, undecane, dodecane, tridecane or structural isomers thereof; hydrocarbons having more than 13 carbon atoms and less than 20 carbon atoms such as hexadecane, eicosane or structural isomers thereof; hydrocarbons such as pseudocumene, petroleum ether, petroleum fractions such as normal paraffins or isoparaffins having an initial boiling point of 150 to 260°C and / or a distillation range of 70°C to 360°C; their halides; fluorine-containing compounds such as hydrofluoroethers; tetraalkylsilane; compounds that generate gas by thermal decomposition by heating, etc. These inner components may be used in combination of one or more. The inner component may be linear, branched or alicyclic, and is preferably aliphatic.

[0103] The hydrocarbon (C1) having 7 to 9 carbon atoms preferably has a boiling point of 80°C to 120°C. The boiling point of the hydrocarbon (C1) having 7 to 9 carbon atoms may be 80°C to 85°C, 90°C to 95°C, and preferably 90°C to 90°C. The boiling point of the hydrocarbon (C1) having 7 to 9 carbon atoms may be 120°C to 115°C, 110°C to 105°C, or 100°C to 100°C, and preferably 110°C to 100°C. By making the hydrocarbon (C1) having 7 to 9 carbon atoms have a boiling point within the above range, expansion characteristics, adhesive characteristics, uncured standing characteristics, etc. can be well exhibited.

[0104] The average boiling point of the inner component may be 40°C or more, 50°C or more, 60°C or more, 70°C or more, 80°C or more, or 90°C or more, preferably 50°C or more, and more preferably 80°C or more. The average boiling point of the inner component may be 150°C or less, 140°C or less, 130°C or less, 120°C or less, 110°C or less, or 100°C or less, preferably 130°C or less, and more preferably 120°C or less. It should be noted that the "average boiling point" refers to the sum of the values ​​obtained by multiplying the boiling points of the components in the inner component by the mass fraction. For example, the average boiling point T of a mixed solvent composed of solvent a (mass Ma, boiling point Ta) and solvent b (mass Mb, boiling point Tb) is obtained by the formula T=Ta×Ma / (Ma+Mb)+Tb×Mb / (Ma+Mb). In this specification, the boiling point refers to the boiling point at normal pressure.

[0105] ·Amount of included ingredients

[0106] The amount of the internal components in the expandable particles (C) may be 5% by weight or more, 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, or 30% by weight or more. The amount of the internal components in the expandable particles (C) may be 65% by weight or less, 55% by weight or less, 45% by weight or less, 35% by weight or less, or 25% by weight or less. The above range is preferred from the viewpoint of the expandability and heat resistance of the expandable particles (C).

[0107] ·The amount of hydrocarbons (C1) having 7 to 9 carbon atoms

[0108] The amount of hydrocarbons (C1) having 7 to 9 carbon atoms in the internal components may be 10% by weight or more, 20% by weight or more, 40% by weight or more, 60% by weight or more, 80% by weight or more, or 95% by weight or more, preferably 40% by weight or more. The amount of hydrocarbons (C1) having 7 to 9 carbon atoms in the internal components may be 100% by weight or less, 95% by weight or less, 90% by weight or less, 80% by weight or less, 70% by weight or less, 60% by weight or less, 50% by weight or less, or 40% by weight or less.

[0109] (Method for producing expandable particles (C))

[0110] The method for producing the expandable particles (C) is not limited, and a known method can be used. As the method for producing the heat-expandable particles (C), the following method can be typically cited, that is, by in-situ polymerization, in the presence of an inner package component as an expansion agent, the above-mentioned monomer is polymerized together with a cross-linking agent as required, and the inner package component is microencapsulated with a polymer. For example, reference can be made to Japanese Patent Application Laid-Open No. 2015-3951, Japanese Patent Application Laid-Open No. 2015-021066, etc.

[0111] (Amount of Expandable Particles (C))

[0112] The amount of the expandable particles (C) in the foamable curable composition may be 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, 3% by weight or more, 5% by weight or more, 8% by weight or more, 10% by weight or more, 15% by weight or more, or 20% by weight or more, or 25% by weight or more, preferably 1% by weight or more. The amount of the expandable particles (C) in the foamable curable composition may be 45% by weight or less, 40% by weight or less, 35% by weight or less, 30% by weight or less, 20% by weight or less, or 10% by weight or less, preferably 30% by weight or less.

[0113] [(D) Cross-linking agent]

[0114] The foamable curable composition of the present invention may contain a crosslinking agent (D). The crosslinking agent (D) becomes active by heating and can crosslink thermosetting elastomers (particularly diene polymers). Examples of the crosslinking agent (D) include sulfur, sulfur compounds, oximes, nitroso compounds, quinone compounds, polyamines, peroxides (particularly organic peroxides), etc. The crosslinking agent (D) can be used in combination with a crosslinking aid (zinc oxide, etc.).

[0115] The crosslinking agent (D) preferably contains an organic peroxide. Examples of organic peroxides include ketone peroxides, peroxyketals, hydrogen peroxide, dialkyl peroxides, Facil peroxides, peroxyesters, peroxydicarbonates, and the like. Specific examples include tert-butyl hydroperoxide, p-menthanehydroperoxide, dicumyl peroxide, tert-butyl peroxide, 1,3-bis(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, benzoyl peroxide, and tert-butyl peroxybenzoate.

[0116] (Amount of crosslinking agent (D))

[0117] The amount of the crosslinking agent (D) in the foaming curable composition may be 0.01% by weight or more, 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, 1% by weight or more, 3% by weight or more, 5% by weight or more, 8% by weight or more, or 10% by weight or more, preferably 0.1% by weight or more. The amount of the crosslinking agent (D) in the foaming curable composition may be 25% by weight or less, 20% by weight or less, 10% by weight or less, 5% by weight or less, 2.5% by weight or less, 1% by weight or less, preferably 5% by weight or less.

[0118] [(E) Thermoplastic resin]

[0119] The foamable curable composition of the present invention may contain a thermoplastic resin (E). The thermoplastic resin (E) exists in the form of particles at room temperature and is a resin that can swell and dissolve in the plasticizer when heated. Specific examples include acrylic resins including polymers of alkyl acrylates (the alkyl group is methyl, ethyl, butyl, 2-ethylhexyl, etc.) or alkyl methacrylates (the alkyl group is methyl, ethyl, butyl, lauryl, stearyl, etc.) or copolymers with other acrylic monomers; MBS resin (methyl methacrylate / butadiene / styrene); ionomer resin; AAS resin (acrylonitrile / styrene / special rubber); AES resin (acrylonitrile / EPDM / styrene); AS resin (acrylonitrile / styrene); ABS resin (acrylonitrile / butadiene / styrene); polyurethane resin; polyester resin; vinyl chloride resin or 1,1-dichloroethylene resin (polyvinyl chloride, vinyl chloride-vinyl acetate copolymer, poly-1,1-dichloroethylene, 1,1-dichloroethylene-vinyl acetate copolymer, 1,1-dichloroethylene-vinyl chloride copolymer, etc.); resin particles such as vinyl acetate resin (ethylene vinyl acetate copolymer, vinyl acetate-acrylate copolymer, vinyl chloride-vinyl acetate copolymer), etc.

[0120] The thermoplastic resin (E) may have a core-shell structure, for example, it may be an acrylic resin having a core-shell structure. The core-shell structure may be composed of a shell having a relatively high glass transition temperature (Tg) and a core having a glass transition temperature (Tg) lower than the shell. For example, a thermoplastic resin having a glass transition temperature (Tg) of 75 to 115°C for the shell and a glass transition temperature (Tg) of 50 to 95°C for the core may be mentioned. The core may be a copolymer or various esters of methyl methacrylate and an alkyl acrylate having 2 to 8 carbon atoms (C2 to C8), and the shell may be a methyl methacrylate homopolymer, a copolymer of methyl methacrylate and acrylic acid, or a copolymer of methyl methacrylate, C2 to C8 alkyl acrylate and acrylic acid. Examples of products of the thermoplastic resin (E) having a core-shell structure include Dianal LP-3106 (core-shell structure, core Tg 75°C, shell Tg 85°C, primary particle size 70 μm) and Dianal LP-3202 (core-shell structure, core Tg 85°C, shell Tg 95°C, primary particle size 60 μm).

[0121] (Amount of thermoplastic resin (E))

[0122] The amount of the thermoplastic resin (E) can be 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, 1% by weight or more, 3% by weight or more, 5% by weight or more, 8% by weight or more, or 10% by weight or more in the foaming curable composition, preferably 0.5% by weight or more. The amount of the thermoplastic resin (E) can be 25% by weight or less, 20% by weight or less, 10% by weight or less, 5% by weight or less, 2.5% by weight or less, or 1% by weight or less in the foaming curable composition, preferably 10% by weight or less. By making the amount of the additive within the above range, the cohesive force of the composition during foaming is moderate, and the foaming ratio is easily improved.

[0123] [(F) Plasticizer]

[0124] The foamable curable composition of the present invention may contain a plasticizer (F). The foamable curable composition of the present invention may contain a thermoplastic resin (E) and a plasticizer (F) at the same time. Thus, it is possible to have good foaming properties, adhesive properties, and uncured after-standing properties. As the plasticizer in the present invention, it can be a substance that can swell or dissolve the above-mentioned thermosetting elastomer (A) or thermoplastic resin (E). Examples of plasticizers include phthalates such as di(2-ethylhexyl) phthalate, butyl benzyl phthalate, dinonyl phthalate, diisononyl phthalate, diisodecyl phthalate, undecyl phthalate, diheptyl phthalate, and butyl phthalylbutyl glycolate; aliphatic dibasic acid esters such as dioctyl adipate, didecyl adipate, and dioctyl sebacate; polyglycol benzoates such as polyoxyethylene glycol dibenzoate and polyoxypropylene glycol dibenzoate; phosphoric acid esters such as tributyl phosphate and tricresyl phosphate; alkyl-substituted diphenyl esters, alkyl-substituted triphenyl esters, partially hydrogenated alkyl triphenyl esters, aromatic process oils, pine oil and other hydrocarbons; and the like.

[0125] (Amount of plasticizer (F))

[0126] The amount of the plasticizer (F) in the foaming curable composition may be 3% by weight or more, 5% by weight or more, 10% by weight or more, 20% by weight or more, 30% by weight or more, 40% by weight or more, or 50% by weight or more, preferably 20% by weight or more. The amount of the plasticizer (F) in the foaming curable composition may be 60% by weight or less, 50% by weight or less, 40% by weight or less, 30% by weight or less, 20% by weight or less, or 10% by weight or less, preferably 50% by weight or less.

[0127] [(G) Filler]

[0128] The foaming curable composition of the present invention may contain fillers (G). By adding fillers, adhesion, droop and specific gravity can be adjusted. Examples of fillers (G) include heavy calcium carbonate, surface untreated calcium carbonate, surface treated calcium carbonate (e.g., fatty acid treated calcium carbonate, etc.), fumed silica, hydrophobic silica, precipitated silica, carbon black, talc, mica, clay, glass beads, microspheres, Shirasuballoons, glass balls, silica balls, plastic balls, organic powder coated plastic balls and other balloons; plastic particles, glass fibers, metal fibers and other inorganic fibers; polyethylene fibers, polypropylene fibers and other organic fibers; aluminum borate, silicon carbide, silicon nitride, potassium titanate, graphite, needle-shaped crystalline calcium carbonate, magnesium borate, titanium diboride, chrysotile, wollastonite and other needle-shaped crystalline fillers; aluminum flakes, aluminum powder, iron powder and the like. These may be used alone or in combination of two or more. By including the filler (G), both the shape retaining property and the bubble break suppressing property can be well exhibited.

[0129] (Amount of filler (G))

[0130] The amount of filler (G) in the adhesive may be 5% by weight or more, 10% by weight or more, 20% by weight or more, 30% by weight or more, 40% by weight or more, 50% by weight or more, or 60% by weight or more, preferably 10% by weight or more. The amount of filler (G) in the adhesive may be 80% by weight or less, 70% by weight or less, 60% by weight or less, 50% by weight or less, 40% by weight or less, or 30% by weight or less, preferably 60% by weight or less. By being within the above range, both shape retention and bubble break suppression can be well exhibited.

[0131] [(H) Other ingredients]

[0132] The foaming curable composition of the present invention may contain other components (F) in addition to the above. Examples of other components (F) include colorants; organic solvents (methanol, ethanol, isopropanol, butanol, acetone, methyl ethyl ketone, volatile oil (Ligroin), ethyl acetate, tetrahydrofuran, n-hexane, heptane, isoparaffin-based high-boiling point solvents, etc.); foaming aids (salicylic acid, urea, etc.); adhesives (silane coupling agents such as vinyltrimethoxysilane, vinyltriethoxysilane, aminosilane, mercaptosilane, epoxysilane, epoxy compounds such as glycidyl ether having a polyoxyalkylene skeleton, etc.); vulcanization accelerators (guanidines, aldehyde-amines, aldehyde-amines, thiazoles, sulfenamides, thioureas, thiurams, dithiocarbamates, xanthan gums, etc.); Acid esters (xanthate, etc.); vulcanization accelerators (long-chain fatty acids with more than 12 carbon atoms such as stearic acid, oleic acid and palmitic acid, metal oxides such as zinc oxide, magnesium oxide and lead oxide); anti-aging agents (hindered phenols, thiols, sulfides, dithiocarboxylates, thioureas, thiophosphates, thioaldehydes, etc.); water retaining agents (water, inorganic salt hydrates, etc.); ultraviolet absorbers, light stabilizers (benzotriazoles, hindered amines, etc.); antioxidants (hindered phenols, etc.); thixotropic agents (colloidal silica, organic bentonite, fatty acid amides, hydrogenated castor oil, etc.); polymer components other than the above (thermosetting resins, thermoplastic resins, etc.), etc. They can be used alone or in combination of two or more.

[0133] ((H) Amount of other ingredients)

[0134] The amount of other components (F) can be appropriately selected according to each component. For example, the total amount or each amount of other components (F) can be 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, 3% by weight or more, 5% by weight or more, or 10% by weight or more in the foaming curable composition. In addition, the total amount or each amount of other components (H) can be less than 20% by weight, less than 15% by weight, less than 10% by weight, less than 5% by weight, less than 2.5% by weight, or less than 1% by weight relative to the foaming curable composition.

[0135] [Method for preparing foamable curable composition]

[0136] The foaming curable composition may be prepared by any method that can uniformly disperse and mix the various components, and for example, the composition may be kneaded using a mixer such as a planetary mixer. During preparation, degassing may be performed as necessary.

[0137] [Application of Foaming Curable Composition]

[0138] The foaming curable composition of the present invention can preferably be used as a coating type sound insulation material, which is used to manufacture a sound insulation wall of an article to improve the sound insulation of the article. For example, the foaming curable composition of the present invention is suitable for forming a sound insulation wall on a closed surface that generates noise such as wind noise during driving in the manufacture of vehicle body parts. Since the foaming curable composition of the present invention can be coated, it has advantages over molded products in that it can be automatically coated, can correspond to gaps of various shapes, and can reduce waste such as release paper.

[0139] <Structure and method for producing the structure>

[0140] The structure of the present invention has a portion filled with the above-mentioned foaming curable composition or its foamed cured product. After the foaming curable composition is applied to the inner surface of the gap, it is heated to a curing temperature to foam and cure, thereby filling the gap to form a sound insulation wall. From the viewpoint of the sound insulation effect, it is preferred that the gap is filled more seamlessly after the foaming curable composition is foamed.

[0141] The coating can also be performed by automatic coating by a robot, etc. For example, the robot may have an arm, a pump, a nozzle, a valve, a material storage chamber, etc. The foaming curable composition of the present invention has excellent separation (broken wire property) between the heated foaming filling material in the nozzle and the nozzle during automatic coating.

[0142] The curing temperature may be above 100°C, above 120°C, above 140°C, above 160°C or above 170°C, and may be below 250°C, below 200°C, below 170°C, below 150°C or below 130°C. The curing time (heating time) may be appropriately set to optimize the foaming ratio or curability, and may generally be above 1 minute, above 3 minutes, above 5 minutes, above 10 minutes or above 15 minutes, or may be below 120 minutes, below 60 minutes, below 30 minutes or below 15 minutes. These conditions vary depending on the setting of the manufacturing process or the substrate, and may be appropriately adjusted. The curing temperature for foaming and curing the foaming curable composition of the present invention is generally about 180°C, but due to the popularity of energy saving in recent years, it may sometimes be carried out at low temperatures such as 160°C. For example, when applied to a vehicle body, the curing temperature may sometimes reach a relatively low temperature of 150°C or 130°C without increasing the temperature of the vehicle body structure, and such a low temperature may also be used as the curing temperature. The foamable curable composition of the present invention exhibits good foaming properties and curing properties even in low-temperature curing.

[0143] Examples of substrates that can be coated include inorganic substrates such as glass, glass ceramics, concrete, mortar, bricks, tiles, gypsum and natural stone (e.g., granite or marble); metals or alloys such as steel, aluminum, iron, copper, titanium, magnesium, and plated metals; organic substrates such as wood, various resins (PVC, polycarbonate, PMMA, polyester, epoxy resin, etc.), glass fiber reinforced plastics (GFP), carbon fiber reinforced plastics (CFP); powder-coated metal or resin coated substrates, etc.

[0144] Examples of the structure include articles with a void portion, particularly articles with a void portion of a closed surface structure. Specific examples of the structure include vehicle body parts, industrial machinery, home appliances, building parts, and the like, preferably vehicle body parts or automobiles such as front pillars (A pillars), center pillars (B pillars), rear pillars (C pillars), wheel covers (Foil arches) (tire houses), and side beams.

[0145] Although the embodiments have been described above, it should be understood that various modifications may be made to the aspects and details without departing from the spirit and scope of the claims.

[0146] [Example]

[0147] Hereinafter, the present invention will be described in detail with reference to Examples, but the present invention is not limited to these Examples.

[0148] [Evaluation test]

[0149] The procedure of the evaluation test is as follows.

[0150] (Exothermic foaming peak temperature of chemical foaming agent)

[0151] The compositions of Examples and Comparative Examples were used as samples and heated from 25° C. to 250° C. at 20° C. / min using Q2000 manufactured by TA Instruments Japan Ltd. The decomposition exothermic peak temperature was taken as the foaming peak temperature of the chemical foaming agent.

[0152] (Expansion Peak Temperature of Expandable Particles of Each Composition)

[0153] Each expandable particle was used as a sample and heated from 25° C. to 250° C. at 20° C. / min using Q2000 manufactured by TA Instruments Japan Ltd. The endothermic peak temperature was defined as the expansion peak temperature of the expandable particle.

[0154] (Peak temperature difference)

[0155] The peak temperature difference is calculated from [foaming peak temperature of the chemical foaming agent] - [expansion peak temperature of the expandable particles].

[0156] (Viscosity)

[0157] Using an extrusion viscosity measuring device (ASTM D1092), the shear rate was determined at 23°C and 50% RH for 20 seconds. -1 Viscosity.

[0158] (Foaming ratio (initial))

[0159] The composition was applied in a sheet of 100×100×1.5 mm in the middle of a 300×300×0.8 mm steel plate, and foamed and cured for 20 minutes at the curing temperature listed in Table 2. The maximum foamed thickness after standing at room temperature for 1 hour was measured, and the foaming ratio was calculated from the thickness before foaming.

[0160] Thickness during coating: t1

[0161] Thickness after solidification and cooling: t2

[0162] Foaming ratio = t2 ÷ t1

[0163] (Uncured storage test 50℃×humidity 95%×30 days)

[0164] The material coated in the same manner as above was left to stand at 50°C and 95% humidity for 30 days, and then foamed and cured at the curing temperature shown in Table 2 for 20 minutes to determine the foaming ratio.

[0165] (Adhesion)

[0166] Using a 25×100×1 mm2 steel plate, the material was cured for 20 minutes at a temperature listed in Table 2 with a gap thickness of 3 mm, an overlap width of 25×25 mm, and a material coating thickness of 1.5 mm. The shear strength was measured according to the 9.20 shear adhesion test method of JASO M323-77.

[0167] (Heat aging resistance test)

[0168] The test piece prepared and cured for the above-mentioned adhesive evaluation was left at 80°C for 30 days, taken out, left at 23°C and 50% humidity for 24 hours, and then the shear strength was measured.

[0169] (Spray resistance)

[0170] For Figure 1 The test piece shown here is coated with the test material in an area of ​​about 20 mm φ. Figure 2 The test apparatus shown was used to evaluate the spray resistance under the following conditions.

[0171] Spray temperature: 50℃

[0172] Spray Angle: 45°

[0173] Spray pressure: 3kgf / cm 2

[0174] Spraying time: 1 minute

[0175] Nozzle: K9S type PT1 / 4×5.0 manufactured by Katori Group Co., Ltd.

[0176] ○: Material fixation rate is more than 95%

[0177] ×: Material fixation rate is less than 95%

[0178] (Cap filling property)

[0179] The material is coated in a 45×100mm shape on a 200×200×0.8mmt steel plate, such as Figure 3 The configuration is shown. The triangular shape is set to an equilateral triangle with a height of 40 mm. Curing is performed for 20 minutes at the curing temperature described in Table 2, and the filling property of the front end of the triangle is confirmed. It should be noted that regarding the thickness of the coated shape, the standard foaming ratio is 5 mmt for a foaming ratio of 7.5 or more, and 6 mmt for a foaming ratio of less than 7.5.

[0180] ◎: 100% fully filled

[0181] ○: Almost filled including the triangular corners (more than 98% filled)

[0182] △: A gap is formed in part of the corner (filled 90% or more)

[0183] ×: Unfilled areas (less than 90% filled)

[0184] [raw materials]

[0185] The raw materials used are described in detail below.

[0186]

[0187] According to the production method of Japanese Patent Application Laid-Open No. 2015-003951, expandable particles 2 to 6 and 8 are produced by the following method, but the production method of expandable particles is not limited to the following method.

[0188] (Method for producing expandable fine particles 2)

[0189] The following polymerizable monomer, the following polymerization catalyst and the following inner component are mixed to obtain an oily mixture.

[0190] Polymerizable monomers: 96 parts acrylonitrile, 141 parts methacrylonitrile, 15 parts methyl methacrylate, 5 parts isobornyl methacrylate, 0.9 parts trimethylolpropane triacrylate, 0.2 parts 1,9-nonanediol dimethacrylate

[0191] Polymerization catalyst (initiator): 1.5 parts of 1,1'-azobis(cyclohexane 1-carbonitrile), 1.5 parts of dilauryl peroxide

[0192] Ingredients: 40 parts of isooctane

[0193] Be that the colloidal aqueous dispersion medium 1000g of about 1% of 9.8 particulate magnesium hydroxide content and above-mentioned oily mixture are stirred with homogenizing mixer with pH, ​​preparation suspension, by reaction initial pressure 0.3MPa, polymerization temperature 65 ℃ × 18 hour+80 ℃ × 2 hour reaction, obtain comprising the aqueous dispersion medium of heat-expandable microsphere.Adjust processing, washing, filtration, drying by pH, obtain removing the heat-expandable microsphere (heat-expandable particle 2) of impurity.

[0194] (Method for producing expandable fine particles 3)

[0195] Heat-expandable microspheres were obtained in the same manner as the method for producing the expandable particles 2 except that the polymerizable monomer and the inner component were changed as follows.

[0196] Polymerizable monomers: 96 parts acrylonitrile, 141 parts methacrylonitrile, 15 parts methyl methacrylate, 5 parts isobornyl methacrylate, 0.9 parts trimethylolpropane triacrylate, 0.2 parts 1,9-nonanediol dimethacrylate

[0197] Ingredients: 30 parts of isooctane, 10 parts of isopentane

[0198] (Method for producing expandable fine particles 4)

[0199] Heat-expandable microspheres were obtained in the same manner as the method for producing the expandable particles 2 except that the polymerizable monomer and the inner component were changed as follows.

[0200] Polymerizable monomers: 116 parts acrylonitrile, 121 parts methacrylonitrile, 20 parts methyl methacrylate, 1 part trimethylolpropane triacrylate

[0201] Ingredients: 30 parts of heptane

[0202] 1000g of colloidal aqueous dispersion medium containing about 1% of micro-particle magnesium hydroxide at pH 9.8

[0203] (Method for producing expandable fine particles 5)

[0204] Heat-expandable microspheres were obtained in the same manner as the method for producing the expandable particles 2 except that the polymerizable monomer and the inner component were changed as follows.

[0205] Polymerizable monomers: 96 parts acrylonitrile, 141 parts methacrylonitrile, 15 parts methyl methacrylate, 5 parts isobornyl methacrylate, 0.9 parts trimethylolpropane triacrylate, 0.2 parts 1,9-nonanediol dimethacrylate

[0206] Ingredients: 50 parts octane

[0207] (Method for producing expandable fine particles 6)

[0208] Heat-expandable microspheres were obtained in the same manner as the method for producing the expandable particles 2 except that the polymerizable monomer and the inner component were changed as follows.

[0209] Polymerizable monomers: 116 parts acrylonitrile, 121 parts methacrylonitrile, 20 parts methyl methacrylate, 1 part trimethylolpropane triacrylate

[0210] Inner ingredients: 20 parts of 2,2'-dimethyloctane, 5 parts of isopentane

[0211] (Method for producing expandable fine particles 8)

[0212] Heat-expandable microspheres were obtained in the same manner as the method for producing the expandable particles 2 except that the polymerizable monomer and the inner component were changed as follows.

[0213] Polymerizable monomers: 170 parts acrylonitrile, 67 parts methacrylonitrile, 20 parts methyl methacrylate, 1 part ethylene glycol dimethacrylate

[0214] Inner ingredients: 20 parts of isobutane

[0215] [Examples 1 to 10 and Comparative Examples 1 to 5]

[0216] The components were mixed according to the formulation shown in Table 1 below to obtain a foaming curable composition. The above-mentioned evaluation test was performed using the obtained foaming curable composition. The results are shown in Table 2 below.

[0217] [Table 1]

[0218]

[0219] [Table 2]

[0220]

Claims

1. A foamable curable composition, in, The foamable curable composition comprises Thermosetting elastomer (A), Chemical blowing agent (B), and Expandable particles (C) having a shell and an inner component, The inner component includes hydrocarbons having 7 to 9 carbon atoms (C1).

2. The foamable curable composition according to claim 1, in, The average boiling point of the inner component is 50° C. or higher and 130° C. or lower.

3. The foamable curable composition according to claim 1 or 2, in, The hydrocarbon (C1) has a boiling point of 80° C. or higher and 120° C. or lower.

4. The foamable curable composition according to any one of claims 1 to 3, in, The hydrocarbon (C1) comprises isooctane.

5. The foamable curable composition according to any one of claims 1 to 4, in, The foamable curable composition includes a cross-linking agent (D).

6. The foamable curable composition according to any one of claims 1 to 5, in, The crosslinking agent (D) includes at least one selected from the group consisting of peroxides, quinones and sulfur.

7. The foamable curable composition according to any one of claims 1 to 6, in, The thermosetting elastomer (A) is a diene polymer.

8. The foamable curable composition according to any one of claims 1 to 7, in, The foamable curable composition includes a thermoplastic resin (E) and a plasticizer (F).

9. The foamable curable composition according to any one of claims 1 to 8, in, The foaming curable composition has a shear rate of 20 sec at 23°C. -1 The viscosity at that time is 500 Pa·s or more and 3000 Pa·s or less.

10. The foamable curable composition according to any one of claims 1 to 9, in, The foaming curable composition has a foaming ratio of 6.5 times or more and 15 times or less.

11. The foamable curable composition according to any one of claims 1 to 10, in, The peak temperature difference defined by [the foaming peak temperature of the chemical foaming agent (B)] - [the expansion peak temperature of the expandable particles (C)] is -10°C or more and 40°C or less. 12 . The foamable curable composition according to claim 1 , which is used for sound insulation. 13 . A structure having a portion filled with the foamable curable composition according to claim 1 or a foamed cured product thereof.

14. The structure according to claim 13, in, The structure has a closed surface, The closed surface is filled with the foamable curable composition or its foamed cured product, The structure is a vehicle body component or a car.